2018
DOI: 10.1155/2018/9067583
|View full text |Cite
|
Sign up to set email alerts
|

Blood Ammonia Level Correlates with Severity of Cirrhotic Portal Hypertensive Gastropathy

Abstract: Background Portal hypertensive gastropathy (PHG) is a common anomaly with potential for bleeding found in portal hypertension. Blood ammonia levels correlate well with liver disease severity and existence of portosystemic shunts. Increased ammonia results in vasodilation and hepatic stellate cell activation causing and exacerbating portal hypertension. Objective To assess the relation of blood ammonia to the presence and severity of portal hypertensive gastropathy in cirrhosis. Methods This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(58 reference statements)
0
2
0
1
Order By: Relevance
“…Some studies have indicated [20] that the occurrence of PHG is related to staged liver function, and the incidence of PHG is high in patients with Child-Pugh B and C cirrhosis, while the occurrence of PHG has nothing to do with Child-Pugh A. In contrast, El-Kalla et al [11] pointed out that the occurrence and severity of PHG were independent of liver function. Mezawa et al [21] pointed out that PHG was relieved after TIPS, but liver function did not change significantly before or two weeks after surgery, so it was speculated that PHG had no significant relationship with liver function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated [20] that the occurrence of PHG is related to staged liver function, and the incidence of PHG is high in patients with Child-Pugh B and C cirrhosis, while the occurrence of PHG has nothing to do with Child-Pugh A. In contrast, El-Kalla et al [11] pointed out that the occurrence and severity of PHG were independent of liver function. Mezawa et al [21] pointed out that PHG was relieved after TIPS, but liver function did not change significantly before or two weeks after surgery, so it was speculated that PHG had no significant relationship with liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Mandhwani et al [9], Sathar et al [10] and Tiwari et al [2] showed that there was a significant association between the occurrence of PHG and Child-Pugh stage. In contrast, El-Kalla et al [11] found no difference between them with respect to Child-Pugh stage. The major purpose of this study was to retrospectively evaluate the incidence of PHG and explore the relationship between PHG and gender, laboratory parameters, liver function and varicose veins.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, a single-center cross-sectional study involving 381 patients with HCV or hepatitis B virus (HBV)-related cirrhosis revealed that plasma ammonia correlates with the presence and severity of portal hypertensive gastropathy (PHG). Cases with severe PHG had significantly higher levels of blood ammonia (192.69 ± 59.87 vs.151.39 ± 54.37 μg/dL, p=0.026) (24). Despite all the evidence correlating ammonia levels with severity of liver disease (Table 1), there are significant overlaps between different stages that challenges its role as a biomarker for disease staging.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…As consequências da hiperamonemia para a hipertensão portal têm sido estudadas in vitro e in vivo. Foi demonstrado que a diminuição de amônia sérica em um modelo de ratos cirróticos, é capaz de regular negativamente a ativação de células estrelárias do fígado e, consequentemente reduzir fatores fisiopatológicos determinantes no estabelecimento da hipertensão portal, sugerindo a amônia como uma possível terapia alvo para a redução da hipertensão portal (El-Kalla et al, 2018).…”
Section: Sinais Sintomas E Complicações Decorrentes Da Cirroseunclassified